PERANCANGAN TAMAN KECAMATAN DI DESA SUNGAI RADAK II KECAMATAN TERENTANG KABUPATEN KUBU RAYA - Sekar, Sekar; Purnomo, Yudi; Zain, Zairin (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
A sub-district park is a park intended to serve the residents of one sub-district. Parks are public open areas that function as social and aesthetic spaces for ecological, recreational, educational or other activities at the sub-district level. In an effort to design recreational facilities, as well as becoming a tourist attraction for the people of Terentang District, where there is no recreation area in the area, so that it can be realized as the main recreation place for the people of Terentang District. Based on the description above, the people of Terentang District need a recreational facility that has an educational function so that it can provide benefits. Based on the needs of the community, it is necessary to consider designing a